Collaborative Area Monitoring Using Wireless Sensor Networks with Stationary and Mobile Nodes. (13th April 2009) - Lambrou, Theofanis P.; Panayiotou, Christos G.
Abstract : Monitoring a large area with stationary sensor networks requires a very large number of nodes which with current technology implies a prohibitive cost. The motivation of this work is to develop an architecture where a set of mobile sensors will collaborate with the stationary sensors in order to reliably detect and locate an event. The main idea of this collaborative architecture is that the mobile sensors should sample the areas that are least covered (monitored) by the stationary sensors. Furthermore, when stationary sensors have a "suspicion" that an event may have occurred, they report it to a mobile sensor that can move closer to the suspected area and can confirm whether the event has occurred or not. An important component of the proposed architecture is that the mobile nodes autonomously decide their path based on local information (their own beliefs and measurements as well as information collected from the stationary sensors in a neighborhood around them). We believe that this approach is appropriate in the context of wireless sensor networks since it is not feasible to have an accurate global view of the state of the environment.